Effects of NiAl precipitate microstructure, loading axis and temperature on deformation behavior of Fe–Al–Ni single crystals. (December 2019) - Yasuda, Hiroyuki Y.; Edahiro, Taisuke; Takeoka, Naoki; Yoshimoto, Takashi; Mizuno, Masataka; Cho, Ken
Abstract: Effects of size and volume fraction of the B2-type NiAl precipitates on the deformation behavior of Fe–Al–Ni single crystals were investigated. In the crystals with different Ni contents, the fine NiAl phase was precipitated in the bcc matrix with small misfit strain. Strong precipitation hardening occurred due to the difference in primary slip system between the bcc matrix and the NiAl precipitates. Moreover, not only <111> slip but also <001> slip occurred depending on the loading axis, the precipitate morphology and the deformation temperature, though the occurrence of <001> slip is generally impossible in bcc metals. The dependence of the critical resolved shear stress for <111> slip on the precipitate size was consistent with the modified precipitation hardening theory. To understand the precipitation hardening, an antiphase boundary energy of the NiAl precipitates was evaluated by first-principles calculations. Moreover, higher volume fraction of the NiAl precipitates was favorable for the activation of <001> slip. Furthermore, the activated slip system varied with deformation temperature, and therefore, the temperature dependence of the yield stress was closely related to the slip system. Highlights: The size and volume fraction of the NiAl precipitates influence the strength. CRSS for <111> slip is closely related to the APB energy of the precipitates. APB energy of NiAl with Fe was calculated to understand the hardening mechanism. Higher volume fraction of the NiAl precipitates is favorable for <001> slip. The activate slip system depends on the loading axis and deformation temperature.